KARAKTERISTIK KIMIA DAN SENSORIS YOGHURT SARI KACANG MERAH DENGAN PENAMBAHAN SARI BUAH BIT - Tri Suci Utami; Nurrahman Nurrahman; Wikanastri Hersoelistyorini (Jurnal Pangan dan Gizi, 2023)
Red beans have high levels of antioxidant compounds from the isoflavone, anthocyanin, and flavonoid groups. Utilizing red beans as a raw material for yogurt can increase its functional value. One alternative variation of yogurt to attract consumers is by adding beet juice. Beet juice has betalain compounds that are yellow, orange, red, and purple pigments as well as sources of antioxidants. The purpose of this study is to determine the effect of adding beet juice on the chemical and sensory characteristics of red bean yogurt. The research method used is Completely Randomized Design (CRD) single factor with 5 treatments and 5 replications. The research stages begin with the process of making red bean juice, making beet juice, and making yogurt. The addition of beet juice is carried out with varying amounts, namely 0%, 5%, 10%, 15%, and 20%. Analysis consisted of fiber content, antioxidant activity, total acid content, pH value, and sensory analysis. The results of this study indicate that the addition of beet juice has a significant effect on increasing fiber content by 8.53%, antioxidant activity by 29.96% RSA, total acid content by 0.957%, and decreasing pH value to 4.1. Adding beet juice also affects the level of preference for the color and taste of yogurt, but does not affect aroma and texture. The best treatment for red bean yogurt with the addition of beet juice determined based on sensory properties, fiber content, antioxidant activity, total acid content, and pH value; is yogurt with the addition of 15% beet juice